Prevalence and associated factors of hypertension among adult patients in Felege-Hiwot Comprehensive Referral Hospitals, northwest, Ethiopia: a cross-sectional study - Belachew, Amare (BMC Res Notes, 2018)
OBJECTIVE: The main objective of this study was to assess the prevalence and factors associated with hypertension among adult patients in Felege-Hiwot Comprehensive Referral Hospital, northwest Ethiopia, 2018. RESULT: The prevalence of hypertension in the current study area was 27.3%. Known history of cardiac problems [AOR = 6.9; 95% CI (1.24, 11.44)], alcohol consumption [AOR = 2.2; 95% CI (1.04, 5.05)], abdominal obesity [AOR = 2.3; 95% CI (1.02, 5.04)], and obesity [AOR = 4.8; 95% CI (1.12, 8.34)] were factors associated independently with hypertension.